Effect of glatiramer acetate on disease reactivation in MS patients discontinuing natalizumab. Issue 1 (28th June 2012) - Rossi, S.; Motta, C.; Studer, V.; De Chiara, V.; Barbieri, F.; Monteleone, F.; Fornasiero, A.; Coarelli, G.; Bernardi, G.; Cutter, G.; Stüve, O.; Salvetti, M.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose Multiple sclerosis (MS) patients discontinuing natalizumab are at risk of rebound of disease activity. Methods In the present multi‐center, open‐label, non‐randomized, prospective, pilot study, we tested whether treatment with glatiramer acetate (GA) is safe and effective after natalizumab in MS patients. The study was performed at academic tertiary medical centers. Forty active relapsing–remitting MS patients who never failed GA therapy and who discontinued natalizumab after 12–18 months of therapy were enrolled. GA was initiated 4 weeks after the last dose of natalizumab. Results 62.5% of patients were relapse‐free 12 months after GA initiation. Annualized relapse rate and time to relapse were significantly lower than before natalizumab. Notably, the frequency of relapses was significantly lower amongst those patients who had experienced ≤2 relapses the year before initiation of natalizumab therapy, compared with patients who had had three or more relapses. No evidence of rebound was observed in magnetic resonance imaging scans. Furthermore, Expanded Disability Status Scale and Multiple Sclerosis Functional Composite were stable in our patients, again suggesting that 12 months of post‐natalizumab–GA therapy is not associated with clinical deterioration. Conclusions Following discontinuation of natalizumab, 12 months of therapy with GA is safe and well tolerated in MS patients. GA can reduce the risk of early reactivation/rebound of disease activity in this setting.